2007
DOI: 10.1177/002242940705500302
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Pitch-Matching of Junior High Boys

Abstract: The skill of pitch-matching is a prerequisite for even the most casual musical participation. While singing accuracy has been carefully researched at the elementary level, there has been comparatively less research done with adolescents. The purpose of the study described here was to examine the influence of perceptual ability, task demands, and singing range on the pitch-matching performance of adolescent boys in various stages of the voice change. We found significant differences between certain, inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 22 publications
3
50
0
2
Order By: Relevance
“…Geringer (1983) established context for test items by asking children to sing back the final pitch in a simple threemeasure song. Demorest and Clements (2007) adopted a similar procedure, and for comparison they employed a single pitch matching condition that replicated the typical classroom exercise in which the teacher sings a single note and the student attempts to sing it back. This latter pitch condition is also most similar to task demands in classrooms and choral rehearsals, and thus represents the most common kind of pitch matching task.…”
Section: Contextual Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Geringer (1983) established context for test items by asking children to sing back the final pitch in a simple threemeasure song. Demorest and Clements (2007) adopted a similar procedure, and for comparison they employed a single pitch matching condition that replicated the typical classroom exercise in which the teacher sings a single note and the student attempts to sing it back. This latter pitch condition is also most similar to task demands in classrooms and choral rehearsals, and thus represents the most common kind of pitch matching task.…”
Section: Contextual Presentationmentioning
confidence: 99%
“…Geringer (1983) found no significant differences in pitch discrimination based on children's pitch matching ability, though the tasks were relatively simple. Demorest and Clements (2007) reported that the results in these studies may vary due to the relative difficulty of items used, but that most studies have not directly compared tasks. They recommended further examination of taskbased variability in singing accuracy.…”
Section: Contextual Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Algunos muchachos, durante un periodo de tiempo más o menos transitorio, no pueden distinguir bien la altura del sonido (afinación) de diferentes tonos. Las investigaciones indican que esto es algo temporal (Demorest y Clements, 2007). ¿Qué tienen en común los esfuerzos de estos profesores-investigadores?…”
Section: Información Básica Sobre Los Adolescentes Y El Cantounclassified